A NEW ELECTROSTATICALLY ACTUATED LOW VOLTAGE RF MEMS SWITCH - Fathi, Mohammad Bagher; Veladi, Hadi; Golmohammadi, Saeed (European Scientific Journal, ESJ, 2013)
This paper describes the design and simulation of a new low voltage electrostatically actuated RF MEMS switch. The switch structure is designed in such a way that, the inherent limitation of electrostatic actuation is relaxed and the actuation voltage is as low as 3.5 V. The idea is to using a two-step electrostatic actuation mechanism instead of conventional two parallel plate electrostatic actuators. In fact the gap between switch and transmission line is reduced in two steps. In order to investigate the usefulness of the proposed idea, both mechanically and electromagnetically, FEM simulations are carried out and satisfactory results are obtained. The RF characteristics of the switch are as follow; Isolation -12 dB at 30 GHz, Insertion Loss -0.08dB at 30 GHz and return loss was below -20 dB at 30 GHz. The proposed switch in this paper can be a promising choice for low voltage high performance RF MEMS switches.